Answer:
64
Step-by-step explanation:
Marcello sells coupon books to his neighbors
4 neighbors each buy 2 coupon books
Each book have 8 coupons
Therefore the total number of coupons that all neighbors will get can be calculated as follows
Each neighbor will get 16 coupon
Hence the whole neighbors will get
16×4
= 64 coupons
A. The relationship of <7 and <8 are that they are vertical angles, and are congruent.
B. Since vertical angles are congruent, you can form an equation where the two measurements equal each other.
C. 5y-29=3y+19 then plug y into your equation: 5*24-29=91
2y=48 and so: <7 = 180-91=89 (and since <8 is congruent)
y=24 <8 also equals 89
Your second problem:
complementary are two angles that add up to 90 degrees.
<B=x, <A=2x
2x+x=90
3x=90
x=30 so: <B=30 degrees, <A=60 degrees
Your third problem:
1. Since A and B are parallel, angle 3x+7 and angle 4x+5 are same-sided exterior angles. That means that they both add up to 180 degrees. So if you should add the two and make it equal 180
2. 3x+7+4x+5=180
7x+12=180
7x=168
x=24
3. <6 is a corresponding angle with angle 3x+7, meaning that they are congruent. So plug x into 3x+7: 3*24+7=79 and since <6 is congruent to 3x+7, <6=79 degrees
Answer:
Step-by-step explanation:
Volume of the box = x³ +11x² + 20x – 32 I think the ' is a typo for ³
the width is x-1 and the height is x+8
Find an expression for the length
Vol = LWH solve L
Vol / (WH) = L so
L = (x³ +11x² + 20x – 32) / (x-1) (x+8)
so it would help to factor the numerator
(x³ +11x² + 20x – 32) I'm willing to bet (x-1) and (x+8) are factors
but I will plot the equation to find the three roots
(x³ +11x² + 20x – 32) = (x-1) (x+8) (x+4)
L = (x³ +11x² + 20x – 32) / (x-1) (x+8)
= (x-1) (x+8) (x+4) / (x-1) (x+8) the (x-1) and (x+8) cancel out leaving
L = (x + 4)
Answer:
<em>(</em><em>f-g</em><em>)</em><em>(</em><em>x</em><em>)</em><em>=</em><em> </em><em>-3x</em><em>^</em><em>3</em><em> </em><em>+</em><em> </em><em>x</em><em>^</em><em>2</em><em> </em><em>+</em><em> </em><em>6x</em>
<em>(</em><em>f</em><em>+</em><em>g</em><em>)</em><em>(</em><em>×</em><em>)</em><em>=</em><em> </em><em>3x</em><em>^</em><em>3</em><em> </em><em>+</em><em> </em><em>x</em><em>^</em><em>2</em><em> </em><em>+</em><em> </em><em>6x</em>
<em>(</em><em>f</em><em>•</em><em>g</em><em>)</em><em>(</em><em>2</em><em>)</em><em>=</em><em> </em><em>6x</em><em>^</em><em>3</em><em> </em><em>+</em><em> </em><em>36x</em><em>^</em><em>3</em>
Step-by-step explanation:
I hope that helps
Answer:
56lb
Step-by-step explanation:
there are 2000lbs in a ton so a measurement in pounds is more precise